A viabilidade do sistema agroflorestal enquanto ferramenta para qualidade de vida e conservação da biodiversidade - Silva, Ana Paula Ferreira da (2019)
Brazil has a prominent role in the agricultural scenario and is known worldwide as a producer of meat and grains, while its recognition also extends in relation to its biodiversity, whose territory is composed of six terrestrial biomes. Among them, the Atlantic Forest biome, characterized by a landscape that supports a rich biological diversity, albeit with a high degree of fragmentation. This scenario explains the paradox that exists between land use processes motivated by agricultural production and biodiversity conservation. Thus, the need to seek development arrangements that may favor the alignment of this contemporary relationship arises. In an attempt to analyze one of these arrangements, this research appropriated the territory of the Paraná River Biodiversity corridor as an empirical space. The objective, therefore, was to evaluate the prospects for the implementation of agroforestry systems (SAF) in the Paraná River Biodiversity corridor, considering the aspects of family farmers' quality of life and landscape connectivity. Methodologically, the local contexts of SAF were analyzed through a case study, involving semistructured interview and direct observation, reconciling with document analysis. Data analysis was delimited from a qualitative and quantitative approach, through statistical analysis of quality of life and landscape connectivity indicators, and also through the analysis of the corridor synthetic matrix elaborated through the Needsand Satisfiers Matrix, proposed by Max-Neef and collaborators (2012). Quantitative results indicated that the central portion of the corridor is the one with the greatest potential for SAF implementation considering the quality of life and landscape connectivity aspects. In the qualitative context, the limitations that are still faced by different social actors that seek the implementation of SAF in this territory were identified, such as lack of technical assistance and labor. But it is still a potential technique in promoting people's quality of life and landscape connectivity when considering aspects such as proportion of thermal comfort, food security, income complement and ecological trampolines potential.